2016
DOI: 10.4238/gmr.15028343
|View full text |Cite
|
Sign up to set email alerts
|

Identifying significant pathways of hepatitis B virus-related hepatocellular carcinoma based on crosstalk and network pathways

Abstract: ABSTRACT. This study aims to identify significant pathways in hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) based on the pathway network strategy. We proposed a pathway network where a protein-protein interaction (PPI) network was integrated with the crosstalk of pathways. Pathway data were first obtained from background PPI network, Reactome pathway database, and common genes between mRNA differentially expressed genes (DEGs), and miRNA target genes of HBV-related HCC. Pathway interactions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…In this study, an LDA score of 4 was set as the threshold. In addition, to determine the taxonomic relations between bacterial communities in the gut bacteria, the relationship between OTUs was analyzed by Spearman correlation coefficient and R (v3.6.0) software, and the co-occurrence analysis was performed with Cytoscape ( Wen et al, 2016 ). Functional-gene profile was inferred with software package Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) based on 16S rRNA gene cluster survey along the samples accompanied by its relative abundance in each of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, an LDA score of 4 was set as the threshold. In addition, to determine the taxonomic relations between bacterial communities in the gut bacteria, the relationship between OTUs was analyzed by Spearman correlation coefficient and R (v3.6.0) software, and the co-occurrence analysis was performed with Cytoscape ( Wen et al, 2016 ). Functional-gene profile was inferred with software package Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) based on 16S rRNA gene cluster survey along the samples accompanied by its relative abundance in each of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…89 These findings demonstrated that NTN1 increases downstream signalling pathways in hypoxic HCC cells, resulting in EMT activation and the generation of several inflammatory mediators that promote cancer invasion. In addition, Wen et al 90 constructed a pathway network that comprise the miRNA target genes associated with HBV-associated HCC. Among them, the most weight value of NTN1 in signalling pathway and regulation of frizzled proteins (FZD) by ubiquitination, at 0.228.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…In addition, Wen et al. 90 constructed a pathway network that comprise the miRNA target genes associated with HBV‐associated HCC. Among them, the most weight value of NTN1 in signalling pathway and regulation of frizzled proteins (FZD) by ubiquitination, at 0.228.…”
Section: Netrins and Tumoursmentioning
confidence: 99%
“…In recent years, miRNA and mRNA expression profile studies have identified a large number of genes with differential expression in HCC (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Numerous differentially expressed miRNAs and mRNAs have been identified to be involved in the occurrence and development of HCC, and thus may be potential prognostic and diagnostic markers (17,26).…”
Section: Introductionmentioning
confidence: 99%